Proposal of a special urban plan for the Macrosector zone in the center of Barquisimeto, Lara State (Gaceta Técnica, 2020)
This article is about the elaboration of a special plan for a zone of the Macrosector Center of Barquisimeto, derived from a situational analysis of the urban structure, social organization, resident population, roads and requirements of urban equipment. Elements of both traditional and strategic planning were combined in a complementary way. In order to create an urban, organized, planned and sustainable space, where the needs and requirements of its inhabitants are covered in the economic, social and cultural aspects, and where their rights and duties as citizens are promoted both today and in the course of the next ten years. The proposed strategic guidelines seek to promote the execution of the action program over time and identifying the public, private or social organizations that will lead each action. This study ends with a proposal that is specified in two housing projects in accordance with the urban environment and current urban regulations
Keywords: urban planification; housing project; urban planification; housing project; Macrosector-center